Mathematical Model of the Three-Phase Induction Machine for the Study of Steady-State and Transient Duty Under Balanced and Unbalanced States - Simion, Alecsandru; Livadaru, Leonard; Munteanu, Adrian (IntechOpen, 2012)
None